Pengaruh Edukasi Flashcard terhadap Tingkat Pengetahuan Terkait Dysmenorrhea pada Mahasiswa Kesehatan dan Non Kesehatan Unair - Roudhotul Jannah; Trias Mahmudiono (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Dysmenorrhea is pain that occurs before, after, or during menstruation. The occurrence of dysmenorrhea in adolescents, especially college students, often hinders the activities that these students must perform and can lead to diseases of the reproductive system. However, dysmenorrhea is often considered a common disease, and its effects are not well understood. This study aims to analyze the effect of education using flashcards related to high calcium and magnesium diets, as well as exercise, on the severity of dysmenorrhea and knowledge levels among health and non-health students at Airlangga University. The method used in this study is experimental with a Quasi-Experimental design and a pretest-posttest control group design among health and non-health students at Airlangga University. The instruments used in this study include questionnaires, flashcards, and a recipe book. The results of this study indicate significant changes in knowledge before and after education, and significant differences in knowledge between the treatment group and the control group. The conclusion of this study is that education using flash cards can be used to improve knowledge and behavior in both groups, both health and non-health students. Therefore, it is recommended that universities conduct regular education programs related to diseases that are still underestimated by the general public